Bloom Where You’re Planted: Spreading the Seeds of Leader in Me Everywhere - Bennett, Carol (Journal of Leadership, Accountability and Ethics, 2020)
There are over 4,000 schools in the Leader in Me process worldwide. This study explored the Leader in Me process in schools specifically in Hawaii, to discover the effect on academic achievement, as well as, behavior according to participating school principals’ perceptions. This study adds to the sparse literature exploring the Leader in Me process. Teacher satisfaction, greater communication and collaboration, improved student behavior, greater parent involvement, more feelings of empowerment, and positive school environment were all strong indicators. As has been noted in similar studies, greater time in the Leader in Me process indicates more positive results.